Long-Term Colonization of the Cystic Fibrosis Lung by Burkholderia cepacia Complex Bacteria: Epidemiology, Clonal Variation, and Genome-Wide Expression Alterations - Coutinho, Carla P.; dos Santos, Sandra C.; Madeira, Andreia; Mira, Nuno P.; Moreira, Ana S.; Sá-Correia, Isabel (Frontiers in Cellular and Infection Microbiology, 2011)
Long-term respiratory infections with Burkholderia cepacia complex (Bcc) bacteria in cystic fibrosis (CF) patients generally lead to a more rapid decline in lung function and, in some cases, to a fatal necrotizing pneumonia known as the “cepacia syndrome.” Bcc bacteria are ubiquitous in the environment and are recognized as serious opportunistic pathogens that are virtually impossible to eradicate from the CF lung, posing a serious clinical threat. The epidemiological survey of Bcc bacteria involved in respiratory infections at the major Portuguese CF Treatment Center at Santa Maria Hospital, in Lisbon, has been carried out by our research group for the past 16 years, covering over 500 clinical isolates where B. cepacia and B. cenocepacia are the predominant species, with B. stabilis, B. contaminans, B. dolosa, and B. multivorans also represented. The systematic and longitudinal study of this CF population during such an extended period of time represents a unique case–study, comprehending 41 Bcc-infected patients (29 pediatric and 12 adult) of whom around 70% have been persistently colonized between 7 months and 9 years. During chronic infection, the CF airways represent an evolving ecosystem, with multiple phenotypic variants emerging from the clonal population and becoming established in the patients’ airways as the result of genetic adaptation. Understanding the evolutionary mechanisms involved is crucial for an improved therapeutic outcome of chronic infections in CF. This review focuses on our contribution to the understanding of these adaptive mechanisms based on extensive phenotypic, genotypic, and genome-wide expression approaches of selected Bcc clonal variants obtained during long-term colonization of the CF airways.